NURSE ENGAGEMENT DI RSU APRILLIA CILACAP - Bhintani Embriana; Andreasta Meliala; Widyawati (Journal of Health Service Management, 2021)
Background: The success of the hospital industry, especially health services, depends on the participation of nurses in providing quality services to patients. In improving the quality of nurse services, hospital management must maximize nurses’ effectiveness, productivity, and innovation by encouraging positive attitudes in work by increasing nurse engagement. At RSU Aprillia Cilacap, the role of nurses is needed, which is shown through vigor, dedication and absorption. Objective: This study measured the relationship between the variables of nurse engagement with the performance of nurses in inpatient installations. Methods: Analytical descriptive quantitative research with cross sectional research design and research sample was 40 nurses. The study measuring instrument is a questionnaire. The sampling technique used was a survey technique carried out by distributing questionnaires with a Likert Scale, involving the entire research sample. Data analysis used cross-tabulation of respondent characteristics on nurse engagement and nurse performance and bivariate analysis using the Chi-Square test (x2 ). Results: There is no correlation between vigor and nurse performance (significance value (p) = 0.061 > 0.05), no correlation between dedication and nurse performance (significance value (p)= 0.291 > 0.05), and there is a correlation between absorption and nurse performance (value of significance). significancy (p) = 0.029 < 0.05). Conclusion: The majority of nurses are at the level of engagement and nurse performance in the medium category. Thus, the manage ment needs to increase the engagement and performance of nurses by implementing nurse engagement with a work contract or MOU for new employees who have completed orientation and old employees who have been appointed as employees. Management needs to do retention so that potential nurses remain obedient and contribute generously to the hospital. The nurse recruitment process requires re-evaluation to obtain quality human resources and have values following the hospital’s vision, mission and goals.